MEASUREMENT OF THE WW-GAMMA GAUGE BOSON COUPLINGS IN P(P)OVER-BAR COLLISIONS AT ROOT-S=1.8 TEV - Abachi, S; Abbott, B; Abolins, M; Acharya, B; Adam, I; Adams, D; Adams, M; Ahn, S; Aihara, H; Alitti, J; Alvarez, G; Alves, G; et al. (1995)
The WW gauge boson couplings were measured using pp» +X (=e,) events at s=1.8 TeV observed with the D0 detector at the Fermilab Tevatron Collider. The signal, obtained from the data corresponding to an integrated luminosity of 13.8 pb-1, agrees well with the standard model prediction. A fit to the photon transverse energy spectrum yields limits at the 95% confidence level on the CP-conserving anomalous coupling parameters of -1.6< <1.8 (=0) and -0.6< <0.6 (=0). Similar limits are obtained for the CP-violating coupling parameters. © 1995 The American Physical Society.